2017
DOI: 10.1145/3133883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and improving semistructured merge

Abstract: While unstructured merge tools rely only on textual analysis to detect and resolve conflicts, semistructured merge tools go further by partially exploiting the syntactic structure and semantics of the involved artifacts. Previous studies compare these merge approaches with respect to the number of reported conflicts, showing, for most projects and merge situations, reduction in favor of semistructured merge. However, these studies do not investigate whether this reduction actually leads to integration effort r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Both studies found that semi-structured merge techniques can reduce the number of conflicts by approximately half, but not eliminate them. Cavalcante et al [44] used the findings from their previous study to improve their semi-structured merge technique to address conflicts involving import declarations and initialization blocks. Although important, the studies by Leßenich et al and…”
Section: Related Workmentioning
confidence: 99%
“…Both studies found that semi-structured merge techniques can reduce the number of conflicts by approximately half, but not eliminate them. Cavalcante et al [44] used the findings from their previous study to improve their semi-structured merge technique to address conflicts involving import declarations and initialization blocks. Although important, the studies by Leßenich et al and…”
Section: Related Workmentioning
confidence: 99%
“…In particular, regardless of the size of the Java projects, 50% of them have infrequent commits. This finding is particularly relevant because if developers take too much time to commit to master (e.g., when working locally or on other branches), they may have to deal with merge conflicts more frequently, which not only require substantial effort from them but also hinder software development activities [18] However, this finding does not ring true when considering Ruby projects. Large Ruby projects, in particular, tend to be more active than the other ones.…”
Section: A Rq1: How Common Is Running CI In the Master Branch But Wimentioning
confidence: 99%
“…Previous studies compared the above merge techniques in practice in terms of speed, quality of resolutions, and the complexity of reported conflicts. For example, Cavalcanti et al [27] focused on unstructured and semi-structured merge tools and found that using semi-structured merge significantly reduces the number of conflicts. The authors also found that the output of semi-structured merge is easier to understand and resolve.…”
Section: B Empirical Studies On Software Mergingmentioning
confidence: 99%